The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.marstruc.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the ductile-brittle fracture transition in steel structures with large shell elements: A numerical study

Abstract: In this paper, the strain energy density (SED) criterion is proposed for predicting the ductilebrittle fracture transition (DBFT) in ships and offshore structures. In finite element simulations, these structures are discretized by relatively large shell elements which precludes the modelling of the local stress and strain states in the vicinity of a crack. Critical values of the SED are determined based on local simulations of fracture for a range of temperatures and plane stress states. The local simulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…On this account, knowledge about the structural performance of steel members subject to the spillage of cryogenic liquids is limited. A few studies in recent years have investigated the structural behaviour of steel at low temperatures (Berejnoi and Ipiña 2015;Majzoobi et al 2016;Bruchhausen et al 2017;Paik et al 2017;Nam et al 2018;Li et al 2019;Paik et al 2020). These studies confirmed the risk of ductile-to-brittle fracture transition in steel at cryogenic temperatures, which might lead to disastrous structural failures in LNG carriers and offshore structures.…”
Section: Introductionmentioning
confidence: 85%
“…On this account, knowledge about the structural performance of steel members subject to the spillage of cryogenic liquids is limited. A few studies in recent years have investigated the structural behaviour of steel at low temperatures (Berejnoi and Ipiña 2015;Majzoobi et al 2016;Bruchhausen et al 2017;Paik et al 2017;Nam et al 2018;Li et al 2019;Paik et al 2020). These studies confirmed the risk of ductile-to-brittle fracture transition in steel at cryogenic temperatures, which might lead to disastrous structural failures in LNG carriers and offshore structures.…”
Section: Introductionmentioning
confidence: 85%
“…It is recognised that structural steel behaviour is predominantly ductile at temperatures higher than the temperature of the ductile-to-brittle fracture transition, as shown in Figure 1. As the temperature decreases approaching cryogenic condition, the material behaves predominantly in a brittle manner with partial or no ductility [33][34][35][36][37][38][39][40]. Majzoobi et al [41] observed that the ductile-to-brittle fracture transition of carbon steel occurs at about -80°C, and the material behaviour becomes entirely brittle at -196°C.…”
Section: Literature Survey On Structural Behaviour At Cold (Sub-zero) Temperaturesmentioning
confidence: 99%
“…modelling the weld toes using shell elements along the plate-stiffener junction. A similar approach was used to model weld toes by Kim et al [44] and Nam et al [35].…”
Section: Figure 18mentioning
confidence: 99%
“…Therefore, for a safer Accidental Limit State (ALS) design of ships and offshore structures, it is necessary to accurately predict their performance in cryogenic conditions. Thus far, a number of experimental and numerical studies have investigated the structural performance of offshore structures and ships in low or cryogenic temperatures (Ehlers and Østby 2012;Nam et al 2018;Paik et al 2020). In these studies, uniform temperature, was applied throughout the structure (i.e.…”
Section: Introductionmentioning
confidence: 99%